THE PHILOSOPHY OF UNIVERSAL HUMAN VALUES IN THE POLICY OF AMIR TEMUR - Alimardanov, Tulkin Turdievich; Kakhkhorova, Matlyuba Mannofovna; Hujamurodov, Tursunpulat Egamberdievich; Tashpulatovna, Turgunova Aziza; Rixsivoevna, Sultanova Aziza (International Journal of Psychosocial Rehabilitation, 2020)
In this article, scientific facts are put forward, which served as the basis for the development of universal human values in Central Asia. Namely, in Uzbekistan, from ancient times, there were various religions like Zoroastrianism, Nestorianism, Tangriism, Buddhism, Shamanism, Judaism and many other spiritual movements, which later became the property of the cultural heritage of this region. The article analyzes the trends and dynamics of interweaving, as well as the identity of different religious cultures with local customs and traditions, which later enriched even the Islamic ideas of universal human values. It was in such religious and social conditions that the great Amir Temur was born. Thus, it is revealed and substantiated from scientific sources that various cultural heritage and teachings directly influenced the formation of the political philosophy of the outstanding statesman and commander. The article carries out historical and comparative analyzes on the basis of “Temur tuzuklari”, considers goals and means, principles, the embodiment of the idea of universal human values in the management of the state and society. In particular, scientific analyses are given that the political idea of Amir Temur manifests and permeates the philosophical traditions of different cultures. In this respect, the great king was deeply devoted to the traditions that from ancient times were the property of the socio-political life of the people of Mawaraannahr. Thus, the study draws scientific conclusions that, in the development and strengthening of the political governance of the state and society, the philosophy of the universal human values of Amir Temur. Today they are a valuable legacy in understanding the essence of national traditions in modern conditions in the creation and development of a democratic society.